A NOVEL ANTIMICROBIAL AGENTS TRICHOSANTHES DIOICA - PRASHANT KUMAR RAI; SHIKHA MEHTA; RAJESH KUMAR GUPTA; GEETA WATAL (International Journal of Pharma and Bio Sciences, 2010)
It is estimated that one-third of the world’s population is infected with tuberculosis (TB). Though a number of drugs have been introduced in past thirty years but still there are unmet needs to develop more effective novel anti-TB drugs. The selection of Trichosanthes dioica plant for the present study was based on its previously identified bioactive potential by our research group. This study deals with the in vitro assessment of antimicrobial activity of different concentration of extract of different part of Trichosanthes dioica. Five clinical isolates of different bacterial strains were used and the disc diffusion method was opted. The results reveal that leaves, fruits and seeds, all three parts of Trichosanthes dioica plant, can be used as anti-bacterial agents. Though the leaves extract was active against all five strains and the highest inhibition was observed against Mycobacterium smegmatis. Thus the leaves extract could be used for tuberculosis treatment.